Availability of support systems for youth who left child and youth care centres during COVID-19 - Fadzaishe B. Zingwe; Maditobane R. Lekganyane (Health SA Gesondheid: Journal of Interdisciplinary Health Sciences)
Background: Youth who left child and youth care centres (CYCCs) during the coronavirus disease 2019 (COVID-19) were exposed to unique scale of challenges compared to their peers. Their transition period required them to have solid plans for their uncertain future towards independence. In further compounding their challenges was their being indeterminate given the uncertainties associated with COVID-19. It was therefore, essential for them to have the necessary support systems to aid them both during their period in care as well as when they left these centres.